Reference World Atlas : Everything You Need to Know About Our Planet Today - Edited by Mumford, Simon (Great Britian Penguin Random House, 2016)
Featuring over 640 maps created with the digital mapping techniques, this book provides an overview of the physical, political, economic and demographic geography of the world.
Include Map, Glossary and Index
Keywords: Map -- Earth (Planet) -- Atlases